Caracterização do perfil peptídico e redução do gosto amargo do hidrolisado de farelo de soja - Ströher, Raquel (2014)
Despite being a rich source of protein, soybean meal is for the most part, intended for use as protein supplement in animal feed. Given the broad availability of this source of protein and the growing interest in the search for components and food additives, there is the modification process for the production of enzymatic hydrolysates of soybean meal in place of traditional chemical processes to extract protein. However, the disadvantage resulting from this reaction of catalysis is the emergence of bitter taste that is considered a major obstacle to the widespread application of these hydrolysates in diets. Thus, several studies have been done to prevent, remove, eliminate or mask the bitter taste of peptides that limit the acceptability of these hydrolysates. Given the above, this study aims to obtain the hydrolysate of soybean meal with pleasant sensory characteristics, enabling its use as a food ingredient. For this purpose, the characterization of soybean meal and hydrolysate obtained via enzymatic reaction was performed. The enzymatic hydrolysate obtained in the conditions defined as optimal using 1.00 % enzyme Alcalase® 2.4L and 2 hours of reaction is mostly composed of peptides in the molecular range between 2.86 and 6.50 kDa. Both treatments used to reduce bitterness, adsorption with activated charcoal and addition of cyclodextrins, were efficient because their capacity of promote interactions between peptides and free amino acids from enzymatic hydrolysate of soybean meal. The activated charcoal can be considered an alternative to the treatment of the hydrolysate because it reduced significantly the concentration of peptides in the molecular range studied within 1 hour percolation of the adsorbate by the fixed bed of charcoal. The cyclodextrins can also be considered as an option of hydrolysate treatment option, because they interact with the molecules in the material, resulting in better bioavailability of this ingredient. The addition of 2.0 % of ?-cyclodextrin in the solution resulted in a reduction of 49% of the free amino acids levels in the hydrolysate. The sensory tests indicated a good acceptance among tasters of formulations prepared with samples of hydrolysates subjected to treatments with activated carbon and the ?-cyclodextrin, which can be verified by the classification of average scores obtained on a hedonic scale, 7.82 and 8.04, respectively.